Coordination and benefit sharing in a three-echelon distribution channel with deteriorating product. (November 2017) - Panda, Shibaji; Modak, Nikunja Mohan; Cárdenas-Barrón, Leopoldo Eduardo
Highlights: This paper proposes two hybrid contract-bargaining processes aiming at channel coordination. The hybrid contract consists of quantity discount and compensation on deterioration cost. It was found that distributers prefer backward contract-bargaining. It was also found that retailers and manufacturer prefer forward contract-bargaining. A numerical example is presented in order to explains the model. Abstract: This paper proposes two hybrid contract-bargaining processes- backward and forward, aiming at channel coordination and benefit sharing in a manufacturer-multiple distributers-multiple retailers supply chain that deals with a deteriorating product. The hybrid contract consists of quantity discount that the manufacturer provides to distributers and compensation on deterioration cost, which distributers provide to retailers. Although both processes coordinate the channel and distribute benefits, distributers prefer backward contract-bargaining but retailers and manufacturer prefer the other. Moreover, without receiving quantity discounts, distributers can coordinate the channel by providing compensations on deterioration costs, which may be larger than deterioration costs. A numerical example explains the model.